Nomophobia level and affecting factors in male university students - Özalp, Yunus Can; Kurnaz, Rifat; Güler, Osman Murat; İnamlık, Melikşah and Berkmen, Sabahattin Mert and Ataç, Ömer and Hayran, Osman (Journal of Dependence, 2021)
Objective: The aim of this study is to examine the level of nomophobia and factors affecting nomophobia in male university students. Method: This cross-sectional study was applied to 241 male university participants. In the study, data were collected through online questionnaire. The questionnaire form consists of questions about sociodemographic characteristics and the Nomophobia Scale (NMP-Q). Results: 21.2% of the participants are in a health-related section, 42.3% are in a numerical section, and 36.5% are in a verbal section. All of the participants are nomophobic and 28.6% are mild, 57.3% are moderate and 14.1% are severe nomophobic. 20.3% of them use their smartphones for more than 5 hours and as the time spent on the phone increases, their nomophobia levels also increase. As the grade average increases, the level of nomophobia also decreases. Using phones for an average of more than 5 hours a day, having less than 4 books completed out of class per month, having an academic grade point average below 3.00, using Youtube, Facebook, Twitter, and carrying a charger or powerbank along with the nomophobia score are determined as variables. Conclusion: When smart phones used to facilitate daily life are not used correctly, it causes various negative situations such as nomophobia. Besides the benefits of these devices, care should be taken against the risks they contain.